The relationship between corporate social responsibility as perceived by employees and job satisfaction based on Nanjing Coherence Supply Chain Company in China - LI, SIFAN (2017)
Abstract: The study investigates the link between corporate social responsibility (CSR), as perceived by employees, and job satisfaction in Nanjing Coherence Supply Chain Company. In order to determine how CSR, as perceived by employees, influences internal job satisfaction, hierarchical regression analysis is used to probe their potential relationship. Specifically, CSR is split up into three dimensions: CSR to non-social stakeholders, CSR to employees and CSR to customers. These dimensions are each addressed by particular items in a questionnaire. The analysis is solely based on a sample of 121 responses of employees to the questionnaire in a survey conducted in a Nanjing Coherence Supply Chain Company. From the results of regression analysis, the hypotheses are supported.